Handling, processing and marketing of milk in the North western Ethiopian highlands - Alemayehu, Y.A.; Wurzinger, Maria; Tegegne, Azage; Zollitsch, W. (2009)
In order to describe the ways of handling, processing and marketing of milk in urban and peri-urban production systems of the North western Ethiopian highlands, 256 and 54 dairy farms were selected for survey and monitoring data collection, respectively.